2014
DOI: 10.1111/dmcn.12618
|View full text |Cite
|
Sign up to set email alerts
|

Fractional anisotropy alterations in individuals born preterm: a diffusion tensor imaging meta‐analysis

Abstract: ALEActivation likelihood estimate DTI Diffusion tensor imaging SMD Standardized mean difference AIM This meta-analysis explored cerebral microstructural changes in individuals born preterm using fractional anisotropy from diffusion tensor imaging.METHOD We used the activation likelihood estimate (ALE) method for the meta-analysis to locate anatomical regions with white matter abnormalities in a group of individuals born preterm and in term-born comparison participants. A statistical analysis of fractional anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
71
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 58 publications
10
71
3
Order By: Relevance
“…Previous DTI-related meta-analyses used a visualised method named activation likelihood estimate (ALE) to locate regions with white matter abnormalities 35, 36 . Another meta-analysis pooled FA values to investigate the most vulnerable region 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous DTI-related meta-analyses used a visualised method named activation likelihood estimate (ALE) to locate regions with white matter abnormalities 35, 36 . Another meta-analysis pooled FA values to investigate the most vulnerable region 17 .…”
Section: Discussionmentioning
confidence: 99%
“…5,32,33 We found a severe involvement of optic tracts, optic radiations, and posterior corona radiata that could affect the integrity of the afferent sensory visual tracts with much more evidence than previously described. 32,34 Although our recruitment criteria excluded children with major visual problems, visual perceptual difficulties characterize the cognitive profile in children with PVL 35 36 Also the different methodology used in cognitive assessment (developmental quotient versus IQ) may have played a role. This study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Eikenes et al (2011) also found reduced FA in the corpus callosum of 49 VLBW (birth weight < 1500 g) PT-born 12-year olds, when compared to 59 term-born controls [134]. A recent meta-analysis [135] incorporated 232 original studies, for a total of 513 PT-born children, adolescents, and young adults and 309 healthy controls. The analysis used an activation likelihood estimate (ALE) procedure to identify regions of abnormal FA in the corpus callosum.…”
Section: Introductionmentioning
confidence: 99%
“…As Li [135] notes, this may be due at least in part to differences in methodology, including the population of interest, the time at which images are collected, and the manner in which brains are segmented into regions or networks. What is clear is that even uninjured PT-born infants show differences in brain connectivity, both structurally and functionally (as described below).…”
Section: Introductionmentioning
confidence: 99%